1998
DOI: 10.1093/chromsci/36.11.565
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bisphenol A in Water by Micro Liquid--Liquid Extraction Followed by Silylation and Gas Chromatography--Mass Spectrometry Analysis

Abstract: A method for the determination of bisphenol A according to the European Union guideline, which establishes a limit of 0.1 ng/mL for organic pollutants in water, is proposed. The method involves a micro liquid-liquid extraction using dichloromethane followed by a silylation step. Identification and quantitation are performed with gas chromatography-mass spectrometry, using an HP-5MS column. The retention time is 7.02 min. Quantitation is carried out using single-ion monitoring (SIM) at m/z 73, 357, and 372. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…75 times compared to GC-MS. 2 However, the GC-MS method needs large sample volume and a tedious sample preconcentration step. 12,13 Recently, HPLC-ECD has been developed with higher sensitivity of 0.01 ng/ml obtained from BPA standard solution, 18 but to our knowledge, no publication has described the application of HPLC-ECD to the analysis of plastic material.…”
Section: Linearity Precision and Accuracy Of The Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…75 times compared to GC-MS. 2 However, the GC-MS method needs large sample volume and a tedious sample preconcentration step. 12,13 Recently, HPLC-ECD has been developed with higher sensitivity of 0.01 ng/ml obtained from BPA standard solution, 18 but to our knowledge, no publication has described the application of HPLC-ECD to the analysis of plastic material.…”
Section: Linearity Precision and Accuracy Of The Proposed Methodsmentioning
confidence: 99%
“…Till now, no paper has described the simultaneous determination of bisphenolic compounds and 4-NP, except one for BPA and BPF. 11 Among the methods for BPA assay, gas chromatography-mass spectrometry (GC-MS), 2,12,13 high-performance liquid chromatography (HPLC)-fluorometry 14,15 and HPLC-UV 16,17 methods are commonly used. Recently, HPLC-electrochemical detection (ECD) for determination of BPA has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Bisphenol A [2,2-bis(4-hydroxyphenyl) propane or BPA], which is a compound widely used as the monomer for the production of polycarbonate plastics and as a major component of epoxy resin, is widely suspected to act as an ED [2,3]. The BPA originating from the plastic products and various wastewaters has been found in rivers, lakes and ocean [4][5][6]. The adverse influence of BPA on aquatic animal has been of great concern [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Krishnan et al [2]have shown that bisphenol A (BPA) can exhibit xenoestrogenic effects in an in vivo cell culture study. There have been many analytical studies on BPA in water and in solvents from environmental water [3, 4], baby food bottles [5]and plastic waste [6]. Polycarbonate and polysulfone are based on BPA.…”
Section: Introductionmentioning
confidence: 99%